Control of a humanoid robot using Motion Retargeting (Revista de Investigaciones Universidad del Quindío, 2015)
This project implements the control of upper extremities in a humanoid robotic platform using a motion retargeting technique. The system uses a Microsoft Kinect to recognize the operator’s joints; then it performs a coordinate’s transformation, validates the limit angles of the robotic platform and finally it transmits the movements to humanoid platform. The robot has two degrees of freedom in the shoulder, one in the elbow and another one in the waist. Using this project, several movements’ routines can be played by the humanoid robot without using any special marks or cables on the operator, avoiding invasive methods to do so.
Keywords: kinect; motion retargeting; robotic platform; control; houmanoid robot